A beautiful day in the neighborhood : neighborly words of wisdom from Mister Rogers - Rogers, Fred; Junod, Tom (Penguin Books, 2019)
"The beloved host of PBS's Mister Rogers' Neighborhood offers warm words of advice and encouragement, along with reflections on his own childhood"--